Ultimatum Game Behavior in a Social-Preferences Vacuum Chamber - Volker Benndorf; Thomas Große Brinkhaus; Ferdinand von Siemens (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study strategic interaction in an experimental social-preferences vacuum chamber. We mute social preferences by letting participants knowingly interact with computers. Our new design allows for indirect strategic interaction: there are several waves in which computer players inherit the behavior of human players from the previous wave. We apply our method to investigate trembling-hand perfection in a normal-form version of the ultimatum game. We find that behavior remains far off from a trembling-hand perfect equilibrium under selfish preferences even towards the end of our experiment. The likely reasons for our findings are strategic uncertainty and incomplete learning.
Keywords: C92; C72; D91; 330; social preferences; induced-value theory; learning; ultimatum game; strategic interaction